In the equation ${x^4} - p{x^3} + q{x^2} - rx + s = 0$, prove that if the sum of two of the roots is equal to the sum of the other two ${p^3} - 4pq + 8r = 0$; and that if the product of the two of the roots is equal to the product of the other two ${r^2} = {p^2}s$.
Answer
Verified
514.5k+ views
Hint: Use identities of the Quadratic polynomial and simply solve them.
Given: ${x^4} - p{x^3} + q{x^2} - rx + s = 0{\text{ }} \ldots \left( 1 \right)$
Let the four roots of the given quadratic polynomial be $\alpha ,\beta ,\gamma ,\delta $
Case 1: Sum of two roots is equal to the sum of other two roots,
$\therefore \alpha + \delta = \beta + \gamma {\text{ }} \ldots \left( 2 \right)$
General quadratic equation: $a{x^4} + b{x^3} + c{x^2} + dx + e = 0{\text{ }} \ldots \left( 3 \right)$
Comparing equation (1) and (3), we get:
$a = 1,{\text{ }}b = - p,{\text{ }}c = q,{\text{ }}d = - r,{\text{ }}e = s{\text{ }} \ldots \left( 4 \right)$
As we know, the sum of roots of a quadratic equation is $ - \dfrac{b}{a}$ .
$
\Rightarrow \alpha + \beta + \gamma + \delta = - \dfrac{b}{a} \\
\Rightarrow \alpha + \beta + \gamma + \delta = - \left( {\dfrac{{ - p}}{1}} \right){\text{ }}\left( {{\text{using }}\left( 4 \right)} \right) \\
\Rightarrow \alpha + \beta + \gamma + \delta = p \\
\Rightarrow \alpha + \beta = \gamma + \delta = \dfrac{p}{2}{\text{ }}\left( {{\text{using }}\left( 2 \right)} \right) \ldots \ldots \left( 5 \right) \\
$
Also, the sum of products of roots of a quadratic equation is $\dfrac{c}{a}$ .
$
\Rightarrow \alpha \beta + \alpha \gamma + \alpha \delta + \beta \gamma + \beta \delta + \gamma \delta = \dfrac{c}{a} \\
\Rightarrow \left( {\alpha + \delta } \right)\left( {\beta + \gamma } \right) + \alpha \delta + \beta \gamma = q{\text{ }}\left( {{\text{using }}\left( 4 \right)} \right) \\
$
Now, substituting values of $\left( {\alpha + \delta } \right)$and $\left( {\beta + \gamma } \right)$from equation (5), we get:
$
\Rightarrow \left( {\dfrac{p}{2}} \right)\left( {\dfrac{p}{2}} \right) + \alpha \delta + \beta \gamma = q{\text{ }}\left( {{\text{using }}\left( 5 \right)} \right) \\
\Rightarrow \alpha \delta + \beta \gamma = q - \dfrac{{{p^2}}}{4}{\text{ }} \ldots \left( 6 \right) \\
$
Now, the sum of products of roots of a quadratic equation is $r$.
$
\Rightarrow \alpha \beta \gamma + \alpha \beta \delta + \alpha \gamma \delta + \beta \gamma \delta = r \\
\Rightarrow \beta \gamma \left( {\alpha + \delta } \right) + \alpha \delta \left( {\beta + \gamma } \right) = r \\
$
Now, substituting values of $\left( {\alpha + \delta } \right)$and $\left( {\beta + \gamma } \right)$from equation (5), we get:
$ \Rightarrow \beta \gamma \left( {\dfrac{p}{2}} \right) + \alpha \delta \left( {\dfrac{p}{2}} \right) = r{\text{ }}\left( {{\text{using }}\left( 5 \right)} \right)$
Taking $\dfrac{p}{2}$ common, we get:
$ \Rightarrow \dfrac{p}{2}\left( {\beta \gamma + \alpha \delta } \right) = r{\text{ }} \ldots \left( 7 \right)$
Putting value of $\left( {\beta \gamma + \alpha \delta } \right)$from equation (6), we get:
$
\Rightarrow \dfrac{p}{2}\left( {q - \dfrac{{{p^2}}}{4}} \right) = r{\text{ }}\left( {{\text{using }}\left( 6 \right)} \right) \\
\Rightarrow {p^3} - 4pq + 8r = 0 \\
$
Case 2: Product of two roots is equal to the product of other two roots, therefore $\alpha \delta = \beta \gamma {\text{ }} \ldots \left( 8 \right)$
We know: $\alpha \beta \gamma + \alpha \beta \delta + \alpha \gamma \delta + \beta \gamma \delta = r$
$
\Rightarrow \beta \gamma \left( {\alpha + \delta } \right) + \alpha \delta \left( {\beta + \gamma } \right) = r \\
\Rightarrow \alpha \delta \left( {\alpha + \beta + \gamma + \delta } \right) = r \\
\Rightarrow \alpha \delta = \beta \gamma = \dfrac{r}{p}{\text{ }}\left( {\because {\text{sum of roots is p}}} \right) \\
$
Now, $\alpha \beta \gamma \delta = \left( {\alpha \delta } \right)\left( {\beta \gamma } \right)$
Putting values of $\alpha \delta $and $\beta \gamma $, we get:
$\alpha \beta \gamma \delta = \left( {\dfrac{r}{p}} \right)\left( {\dfrac{r}{p}} \right) = s$
$
\therefore \dfrac{{{r^2}}}{{{p^2}}} = s \\
{r^2} = {p^2}s \\
$
Hence Proved.
Note: Whenever there are polynomial equations and you have to prove something related to their roots, always try to use the polynomial identities like sum of roots, product of roots etc. and try to obtain relations between them.
Given: ${x^4} - p{x^3} + q{x^2} - rx + s = 0{\text{ }} \ldots \left( 1 \right)$
Let the four roots of the given quadratic polynomial be $\alpha ,\beta ,\gamma ,\delta $
Case 1: Sum of two roots is equal to the sum of other two roots,
$\therefore \alpha + \delta = \beta + \gamma {\text{ }} \ldots \left( 2 \right)$
General quadratic equation: $a{x^4} + b{x^3} + c{x^2} + dx + e = 0{\text{ }} \ldots \left( 3 \right)$
Comparing equation (1) and (3), we get:
$a = 1,{\text{ }}b = - p,{\text{ }}c = q,{\text{ }}d = - r,{\text{ }}e = s{\text{ }} \ldots \left( 4 \right)$
As we know, the sum of roots of a quadratic equation is $ - \dfrac{b}{a}$ .
$
\Rightarrow \alpha + \beta + \gamma + \delta = - \dfrac{b}{a} \\
\Rightarrow \alpha + \beta + \gamma + \delta = - \left( {\dfrac{{ - p}}{1}} \right){\text{ }}\left( {{\text{using }}\left( 4 \right)} \right) \\
\Rightarrow \alpha + \beta + \gamma + \delta = p \\
\Rightarrow \alpha + \beta = \gamma + \delta = \dfrac{p}{2}{\text{ }}\left( {{\text{using }}\left( 2 \right)} \right) \ldots \ldots \left( 5 \right) \\
$
Also, the sum of products of roots of a quadratic equation is $\dfrac{c}{a}$ .
$
\Rightarrow \alpha \beta + \alpha \gamma + \alpha \delta + \beta \gamma + \beta \delta + \gamma \delta = \dfrac{c}{a} \\
\Rightarrow \left( {\alpha + \delta } \right)\left( {\beta + \gamma } \right) + \alpha \delta + \beta \gamma = q{\text{ }}\left( {{\text{using }}\left( 4 \right)} \right) \\
$
Now, substituting values of $\left( {\alpha + \delta } \right)$and $\left( {\beta + \gamma } \right)$from equation (5), we get:
$
\Rightarrow \left( {\dfrac{p}{2}} \right)\left( {\dfrac{p}{2}} \right) + \alpha \delta + \beta \gamma = q{\text{ }}\left( {{\text{using }}\left( 5 \right)} \right) \\
\Rightarrow \alpha \delta + \beta \gamma = q - \dfrac{{{p^2}}}{4}{\text{ }} \ldots \left( 6 \right) \\
$
Now, the sum of products of roots of a quadratic equation is $r$.
$
\Rightarrow \alpha \beta \gamma + \alpha \beta \delta + \alpha \gamma \delta + \beta \gamma \delta = r \\
\Rightarrow \beta \gamma \left( {\alpha + \delta } \right) + \alpha \delta \left( {\beta + \gamma } \right) = r \\
$
Now, substituting values of $\left( {\alpha + \delta } \right)$and $\left( {\beta + \gamma } \right)$from equation (5), we get:
$ \Rightarrow \beta \gamma \left( {\dfrac{p}{2}} \right) + \alpha \delta \left( {\dfrac{p}{2}} \right) = r{\text{ }}\left( {{\text{using }}\left( 5 \right)} \right)$
Taking $\dfrac{p}{2}$ common, we get:
$ \Rightarrow \dfrac{p}{2}\left( {\beta \gamma + \alpha \delta } \right) = r{\text{ }} \ldots \left( 7 \right)$
Putting value of $\left( {\beta \gamma + \alpha \delta } \right)$from equation (6), we get:
$
\Rightarrow \dfrac{p}{2}\left( {q - \dfrac{{{p^2}}}{4}} \right) = r{\text{ }}\left( {{\text{using }}\left( 6 \right)} \right) \\
\Rightarrow {p^3} - 4pq + 8r = 0 \\
$
Case 2: Product of two roots is equal to the product of other two roots, therefore $\alpha \delta = \beta \gamma {\text{ }} \ldots \left( 8 \right)$
We know: $\alpha \beta \gamma + \alpha \beta \delta + \alpha \gamma \delta + \beta \gamma \delta = r$
$
\Rightarrow \beta \gamma \left( {\alpha + \delta } \right) + \alpha \delta \left( {\beta + \gamma } \right) = r \\
\Rightarrow \alpha \delta \left( {\alpha + \beta + \gamma + \delta } \right) = r \\
\Rightarrow \alpha \delta = \beta \gamma = \dfrac{r}{p}{\text{ }}\left( {\because {\text{sum of roots is p}}} \right) \\
$
Now, $\alpha \beta \gamma \delta = \left( {\alpha \delta } \right)\left( {\beta \gamma } \right)$
Putting values of $\alpha \delta $and $\beta \gamma $, we get:
$\alpha \beta \gamma \delta = \left( {\dfrac{r}{p}} \right)\left( {\dfrac{r}{p}} \right) = s$
$
\therefore \dfrac{{{r^2}}}{{{p^2}}} = s \\
{r^2} = {p^2}s \\
$
Hence Proved.
Note: Whenever there are polynomial equations and you have to prove something related to their roots, always try to use the polynomial identities like sum of roots, product of roots etc. and try to obtain relations between them.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE